The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1007/bf02577116
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transluminal angioplasty of abdominal aortic stenoses

Abstract: Percutaneous transluminal angioplasty (PTA) was performed on 25 patients with localized distal abdominal aortic stenoses. All patients were smokers and all complained of bilateral lower limb claudication. Eleven patients had small distal aortas and iliac vessels. Technically successful dilatation was achieved in all patients. Long-term follow-up was available on 17 of the patients. The mean follow-up period was 38 months. Cumulative patency at 5 years was 70%. Thirteen patients remain asymptomatic 15-83 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 12 publications
1
12
0
2
Order By: Relevance
“…Endovascular treatment of infrarenal aortic stenosis has been proposed [28,29] as a viable alternative to surgical revascularisation since the 1980s, and data available have established the safety and effectiveness of PTA, with an 85% primary and a 90% secondary patency rate [7][8][9][10][11][12] together with a low (3%) risk of major complications, such as vessel-wall rupture and distal and visceral embolism [21]. However, most evidence concerns the treatment of focal (<20-mm) stenoses not involving the distal aortic bifurcation [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Endovascular treatment of infrarenal aortic stenosis has been proposed [28,29] as a viable alternative to surgical revascularisation since the 1980s, and data available have established the safety and effectiveness of PTA, with an 85% primary and a 90% secondary patency rate [7][8][9][10][11][12] together with a low (3%) risk of major complications, such as vessel-wall rupture and distal and visceral embolism [21]. However, most evidence concerns the treatment of focal (<20-mm) stenoses not involving the distal aortic bifurcation [21].…”
Section: Discussionmentioning
confidence: 99%
“…Il trattamento endovascolare delle stenosi dell'aorta sottorenale è stato proposto a partire dal 1980 [28,29] come una valida alternativa alla rivascolarizzazione chirurgica e i dati disponibili in letteratura hanno stabilito l'efficacia della PTA con pervietà primaria dell'85% e secondaria del 90% [7][8][9][10][11][12] e con basso tasso di complicanze maggiori (3%) quali la rottura della parete vasale e l'embolizzazione distale o viscerale [21]. Comunque la maggior parte dei dati riguarda il trattamento di stenosi focali (<20 mm) che non coinvolgevano la biforcazione aortica [21].…”
Section: Discussioneunclassified
See 2 more Smart Citations
“…Recent studies have shown improved clinical outcomes of endovascular therapy in complex iliac lesions involving the aortic bifurcation due to recent advances in devices and skills. [9][10][11][12][13][14][15] However, there are a paucity of data on immediate and long-term outcomes of endovascular treatments of chronic aortic occlusive disease. 16,17 We therefore sought to investigate the immediate and longterm outcomes of endovascular therapy in patients with chronic total occlusion of the infrarenal aorta.…”
mentioning
confidence: 98%